Acute kidney injury associated with immune checkpoint inhibitor therapy: incidence, risk factors and outcomes. Issue 1 (29th June 2020) - Meraz-Muñoz, Alejandro; Amir, Eitan; Ng, Pamela; Avila-Casado, Carmen; Ragobar, Claire; Chan, Christopher; Kim, Joseph; Wald, Ron; Kitchlu, Abhijat
Abstract : Background: Immune checkpoint inhibitors (ICPi) are a novel and promising anti-cancer therapy. There are limited data on the incidence, risk factors and outcomes of acute kidney injury (AKI) in patients receiving ICPi. Methods: We conducted a cohort study of patients receiving ICPi at our center between 2010 and 2017 via electronic health record. The primary outcome was AKI (increase of >50% from baseline serum creatinine (sCr)). Risk factors for AKI were assessed using logistic regression. Survival among those with and without AKI was compared using the Kaplan-Meier method. Results: Among 309 patients on ICPi, 51 (16.5%) developed AKI (Kidney Disease Improving Global Outcomes (KDIGO) stages 1: 53%, 2: 22%, 3: 25%). AKI was associated with other immune-related adverse events (IRAE) (OR 3.2, 95% CI 1.6 to 6; p<0.001), hypertension (OR 4.3, 95% CI 1.8 to 6.1; p<0.001) and cerebrovascular disease (OR 9.2; 95% CI 2.1 to 40; p<0.001). Baseline sCr, cancer, and ICPi type was not associated with AKI. Use of angiotensin-converting enzyme inhibitors/angiotensin-receptor blockers (OR 2.9; 95% CI 1.5 to 5.7; p=0.002), diuretics (OR 4.3; 95% CI 1.9 to 9.8; p<0.001), and corticosteroid treatment (OR 1.9; 95% CI 1.1 to 3.6; p=0.03) were associated with AKI. In the multivariable analysis, AKI was associated only with other IRAE (OR 2.82; 95% CI 1.45 to 5.48; p=0.002) and hypertension (OR 2.96; 95% CI 1.33 to 6.59; p=0.008). AKI was not associated with increased risk of mortality (HR 1.1; 95% CI: 0.8 to 1.6; p=0.67). ICPi nephrotoxicity was attributed via biopsy or nephrologist assessment in 12 patients (six interstitial nephritis, two membranous nephropathy, two minimal change disease, and two thrombotic microangiopathy). Subsequent doses of ICPi were administered to 12 patients with prior AKI, with one (8.3%) having recurrent AKI. Conclusion: AKI is a common complication in patients receiving ICPi treatment. The development of other IRAE and previous diagnosis of hypertension were associated with increased AKI risk. AKI was not associated with worse survival. Distinguishing kidney IRAE from other causes of AKI will present a frequent challenge to oncology and nephrology practitioners. Kidney biopsy should be considered to characterize kidney lesions and guide potential therapy.